Decrease in Hospital Admissions for Transient Ischemic Attack, Mild, and Moderate Stroke During the COVID-19 Era. Issue 8 (August 2020) - Diegoli, Henrique; Magalhães, Pedro S.C.; Martins, Sheila C.O.; Moro, Carla H.C.; França, Paulo H.C.; Safanelli, Juliana; Nagel, Vivian; Venancio, Vanessa G.; Liberato, Rafaela B.; Longo, Alexandre L.
Abstract : Background and Purpose: Since the onset of the coronavirus disease 2019 (COVID-19) pandemic, doctors and public authorities have demonstrated concern about the reduction in quality of care for other health conditions due to social restrictions and lack of resources. Using a population-based stroke registry, we investigated the impact of the onset of the COVID-19 pandemic in stroke admissions in Joinville, Brazil. Methods: Patients admitted after the onset of COVID-19 restrictions in the city (defined as March 17, 2020) were compared with those admitted in 2019. We analyzed differences between stroke incidence, types, severity, reperfusion therapies, and time from stroke onset to admission. Statistical tests were also performed to compare the 30 days before and after COVID-19 to the same period in 2019. Results: We observed a decrease in total stroke admissions from an average of 12.9/100 000 per month in 2019 to 8.3 after COVID-19 ( P =0.0029). When compared with the same period in 2019, there was a 36.4% reduction in stroke admissions. There was no difference in admissions for severe stroke (National Institutes of Health Stroke Scale score >8), intraparenchymal hemorrhage, and subarachnoid hemorrhage. Conclusions: The onset of COVID-19 was correlated with a reduction in admissions for transient, mild, and moderate strokes. Given the need to prevent the worsening of symptoms and the occurrence of medical complications in these groups, a reorganization of the stroke-care networks is necessary to reduce collateral damage caused by COVID-19.